Pemberdayaan Masyarakat Melalui Program CSR PT PJB UBJOM PLTU Tenayan - tutut pujayanti Pujayanti (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2021)
This study aims to determine the implementation process as well as the driving and inhibiting factors of community empowerment through the Corporate Social Responsibility (CSR) program by PT. PJB UBJOM PLTU Tenayan in Industri Tenayan Village. The method used in this research is descriptive qualitative using a case study approach. The data analysis technique used in this study is a qualitative analysis proposed by Miles and Humbberman. The results showed that at the awareness stage, namely by providing understanding to achieve change, increasing a sense of awareness and the formation of the Muda Jaya Organik group. At the capacity stage, they are given training in business management, group structure and legality. Meanwhile, at the empowerment stage, giving power, power, and opportunities in the form of providing assistance for seeds and cages to create independence. The supporting factor is the support from stakeholders both from the government, private sector, and the community. The inhibiting factor is the unavailability of supporting technology in making media and processing results. So that the implementation of empowerment has not been carried out optimally.